Qu’attendre d’une comparaison des scolastiques ? - Vincent Eltschinger (Socio-anthropologie, 2017)
The geographical, cultural and historical context of the study of medieval philosophy has been remarkably extended during the last decades, with “medieval philosophy” referring to all Latin, Islamic, Jewish and Byzantine—i.e. monotheistic—developments from a common philosophical heritage of Neoplatonic and Aristotelian inflection. Under these conditions, what can be done about Buddhist India, which, although it has no genetic relationship with these philosophical traditions of late Antiquity, nevertheless shares essential traits with medieval philosophy: “hermeneutic situation”, relation to authority, the concomitant importance of commentary, the “clericality” of actors, the division of knowledge, the primacy of debate, of logical reflection and linguistics, etc. The purpose of this essay is to explore the possibilities of a comparison between Latin Christian and Indian Buddhist scholasticisms. It argues for a comparative approach to knowledge-producing intellectual cultures rather than dogmas, doctrines and arguments, and to this end draws a brief sketch of Buddhist scholasticism and its institutional environment.